Pengembangan Media Interaktif Dalam Pelatihan Untuk Peningkatan Kinerja Marketing Sepeda Motor Honda Di Banten - Ridhaswara, Elfa; Ruhiat, Yayat; Nurhakim, Lukman (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2025)
The motorcycle industry is a significant economic driver in Indonesia, with Honda as the dominant brand. Recognizing the large market potential and the need for innovative marketing strategies, this research focused on developing interactive media to enhance Honda's sales marketing effectiveness. A 4D development model was employed, consisting of four stages: Define, Design, Develop, and Disseminate. The Define stage involved a thorough analysis of market needs, target consumers, and current trends in motorcycle marketing. The Design stage focused on creating a concept and design for interactive media that is engaging, informative, and user-friendly. In the Develop stage, a prototype of the interactive media was create based on the approved design. Finally, the Disseminate stage involved testing and evaluating the developed interactive media on potential users. The research results showed that the developed interactive media received highly positive evaluations from experts. Language experts gave a score of 95%, indicating excellent language and communication quality. Media experts gave a perfect score of 100%, demonstrating the media's effectiveness and adherence to industry standards. Material experts gave a score of 94%, confirming the accuracy and relevance of the content. Overall, the development of this interactive media was declare